Evidence for enhanced optical properties through plasmon resonance energy transfer in silver silica nanocomposites. (25th January 2016) - Mol, Beena; Joy, Lija K; Thomas, Hysen; Thomas, Vinoy; Joseph, Cyriac; Narayanan, T N; Al-Harthi, Salim; Unnikrishnan, N V; Anantharaman, M R
Abstract: Silver nanoparticles were dispersed in the pores of monolithic mesoporous silica prepared by a modified sol–gel method. Structural and microstructural analyses were carried out by Fourier transform infrared spectroscopy and transmission electron microscopy. X-ray photoelectron spectroscopy was employed to determine the chemical states of silver in the silica matrix. Optical absorption studies show the evolution absorption band around 300 nm for silver (Ag) in a silica matrix and it was found to be redshifted to 422 nm on annealing. Photoluminescence studies indicate the presence of various luminescent emitting centers corresponding to silver ions and silver dimers in the SiO2 matrix. The enhancement of absorption and photoluminescence properties is attributed to plasmon resonance energy transfer from Ag nanoparticles to luminescent species in the matrix.